(3eONd Edi GdJehjd Gdegjcds - (3YeQ(B, (3WGdHs ((3GdLRGFQ (B:s (3OGQ EjdjGA ddfTQ hGdJhRjY(B,s, 2024)
(3GdJehjd Gdegjcd cTcd ef CTcGd GdJehjd GdMOjK h JfGhd GhdG eGgjI GdJehjd Gdegjcd h JWQb KGfjG ddJehjd Gdegjcd h GdefTBJ PGJ GdZQV GdNGU , GeG KGKG eTJbGJ eYOdGJ GdaGFOI h QGHYG eTJbGJ GdGFJeGf , JhQjb GdOjhf GdQgjfI GdYbGQjI GhdG eGgjI GdJhQjb KGfjG gjGcdg , KGdKG eRGjG GdJhQjb HGdfSHI ddGShGb GdeGdjI h GdGbJUGOjI h QGHYG GdGfTZGdGJ GdeJYdbI HBKGQ GdJhQjb Ydi GdGShGb GdeGdjI h GdGbJUGO , CKQ GdJhQHb Ydi COGA CShGb GdGFJeGf GdYbGQj (B- (3GdhdGjGJ GdeJMOI fehPLG GhdG GShGb QGS GdeGd h Gdi Shb GdQgf GdYbGQj , KGfjG CKQ GdJhQjb Ydi JcdaI GdGFJeGf , KGdKG CKQ GdJhQjb Ydi JhGaQ GdGFJeGf h QGHYG CKQ GdJhQjb Ydi JTJJ GdeNGWQ h NGeSG CKQ GdJhQjb Ydi Ydi GdSjhdI (B.s
(3GdeQGLY U(B.371s
Keywords: (3GdGFJeGf GdYbGQjs; (3GdJehjds; (3GdOjhfs